Danos em massa e os punitive damages - BONNA, Alexandre Pereira (Universidade Federal do Pará, 2017)
A rereading of the punitive damages institute is proposed from the perspective of its interface situated between the collective action and the mass damages. It is examined whether the indemnity that arises out of the punitive damage should be handled in a context of collective or individual actions, aiming to satisfactorily answer which of the aforementioned ways is the most suitable, by taking an analysis based on the comparative method, sustained by two factors: the right to proof of the relevant facts to characterize the punitive damages and measuring the degree of reprehensibility of the conduct and the economic theory of punitive damages on the discouragement, based on the theory Polinsky and Shavell. A research is performed assuming that the punitive damages has a place is Brazilian’s legal system based on the theory of law as integrity from Ronald Dworkin, nevertheless, the outline of the punitive damages are searched in the North American Juridical experience as a theoretic base for the comparison made with eyes turned to the Brazilian case. An analysis of the precedents of the Supreme Court of the United States is performed and the relevant facts for the punitive damage are adopted based on the interpretation of such Court. The application profile of the punitive damages in the United States and in Brazil are traced, intending to identify the weak elements in the national legal practice. The requisite of the superiority of the collective actions seen in the North-American experience is brought to Brazilian Law from the perspective of the interest to act and the effectiveness of the process. The meaning of the superiority test is deepened based on the test that exists in the North-American experience with the class actions, which is used in the task to determine if the rights at stake are able of being collectively judged in the context of the class action for individual damages, in other words, the superiority is a requisite for the processing of a class action, implying that the magistrate must evaluate whether the class action is superior to other available proceedings, in terms of justice and efficiency of the decision. Examines the superiority of collective protection for the right proof of the relevant facts to the impact of punitive damages and assessing the degree of reprehensibility of conduct. Assesses the superiority of collective protection under the paper disincentive situated in economic fundamentals of punitive damages. The conceptualization of mass damages is adopted, allocated in the scope of procedural law. It is concluded that when facing individual mass damages produced in a large scale, the most suitable way of obtaining an adequate level of dissuasion and reprehend the behavior of the offender is to make use of the collective action, the same way that the collective actions have proved to be superior because of the legitimacy that lies on the right to evidence of the relevant facts in order to characterize the incidence of the punitive damages and assess the degree of reprehensibility of the conduct.